Penggunaan Multimedia Development Life Cycle dalam Rancang Bangun Media Pembelajaran Toleransi Beragama - Fatimah, Dini Destiani Siti; Mubarok, Muhammad Syauqi; Apriani, Aulia (Jurnal Algoritma, 2024)
As time goes by, interactive media has become an alternative learning method. Learning using interactive media has added value to the educational process, one area of ​​learning that requires innovation is religious learning. The Indonesian government recognizes the existence of religious diversity, where religious tolerance needs to be socialized to its adherents, especially children. Religious tolerance material in terms of various religions can be socialized through information technology-based learning media. This media is classified as interactive media which supports the effectiveness of learning because it utilizes multimedia. The aim of this research is to design learning media regarding religious tolerance using the Multimedia Development Life Cycle method. This method has six stages, namely the concept, design, material collecting, assembly, testing and distribution stages. This application has been tested using functional tests and beta tests carried out with teachers. The test results show that the functions have worked as expected. The results of this research can play a role in understanding children about religious tolerance through religious tolerance material that is appropriate to their respective religions.